Laser finishing of 3D printed parts produced by material extrusion. (January 2020) - Lambiase, F.; Genna, S.; Leone, C.
Highlights: Laser surface finishing of polymeric component made by material extrusion was studied. The surface roughness and the ablated depth were measured. Analysis of variance was adopted to evaluate the effect of the process parameters. Response Surface Method and Master Response Optimisation were adopted to optimise the process. A significant reduction of the roughness and a limited surface recession were obtained. Abstract: Laser surface finishing of 3D printed components made by material extrusion is investigated. A 30W CO2 laser source, working in continuous wave (CW) mode, was employed to treat the surface of components made of Polylactic acid (PLA) obtained by material extrusion (ME). The mechanism of surface finishing was investigated and the influence of the laser treatment parameters (scanning speed, energy density and hatch distance) on the surface morphology was determined. The surface of treated samples was characterized by means of roughness measurements and optical microscopy. The results indicated that laser finishing was capable to improve significantly the surface roughness (more than ten times). However, interaction mechanisms involve surface ablation. ANalysis of VAriance (ANoVA) was performed to determine the influence of the process parameters on the surface characteristics. In addition, Response Surface Method (RSM) and Multi-Response Optimization (MRO) were adopted to determine the optimum process conditions. Thus, process conditions that enabled to enhance the surface roughness (form Ra = 16 μm for untreated surface to Ra = 0.3 μm under optimal process conditions) and minimize the surface recession (0.1 mm) were determined.